The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1038/nnano.2011.191
|View full text |Cite
|
Sign up to set email alerts
|

Role of cell cycle on the cellular uptake and dilution of nanoparticles in a cell population

Abstract: Nanoparticles are considered a primary vehicle for targeted therapies because they can pass biological barriers and enter and distribute within cells by energy-dependent pathways. So far, most studies have shown that nanoparticle properties, such as size and surface, can influence how cells internalize nanoparticles. Here, we show that uptake of nanoparticles by cells is also influenced by their cell cycle phase. Although cells in different phases of the cell cycle were found to internalize nanoparticles at si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

39
529
1
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 555 publications
(586 citation statements)
references
References 36 publications
39
529
1
1
Order By: Relevance
“…1,9,26,[40][41][42][43][44] Figure 1 shows a comparison of the kinetics of uptake of silica nanoparticles in A549 cells in serum free and complete media, obtained by flow cytometry, as described in the Methods. As anticipated in Supplementary Figure S1, the kinetic study also clearly indicated that uptake was always higher when the nanoparticles were exposed to cells in SF.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1,9,26,[40][41][42][43][44] Figure 1 shows a comparison of the kinetics of uptake of silica nanoparticles in A549 cells in serum free and complete media, obtained by flow cytometry, as described in the Methods. As anticipated in Supplementary Figure S1, the kinetic study also clearly indicated that uptake was always higher when the nanoparticles were exposed to cells in SF.…”
Section: Resultsmentioning
confidence: 99%
“…Their characterisation in the same media is reported elsewhere. 1,40,42 Cell Culture A549 cells (original batches from ATCC, item number CCL-185) were cultured at 37 °C in 5% CO 2 in complete medium (cMEM), prepared as described above. Human glial astrocytoma 1321N1 cells (passage 2-10) and Human cervix epithelium HeLa cells (passage 5-10) were cultured at 37 ºC in 5% …”
Section: Nanoparticle Characterisationmentioning
confidence: 99%
“…4C). Nanoparticles also affect cell cycle progression [5,6], which is closely related to cell uptake of MNP [49]. Cytometric analysis of the cell cycle showed that 100 µM BPA led to an increase in the sub-G1 population (>40%) and a decrease in G0-G1 (∼30%) and S (∼10%) populations compared to untreated controls (Fig.…”
Section: In Vitro Dmsa-mnp Cytotoxicitymentioning
confidence: 92%
“…Still, silencing also shows that a portion of uptake does not depend on TfR, and this is consistent with the limited colocalization with TfR observed in Fig.1c. Nanoparticle export 31 appears absent (Fig.1e), at least for time scales comparable to Tf export (shown in Supplementary Fig. S2d), and nanoparticles accumulate in the lysosomes (Fig.…”
mentioning
confidence: 87%